Transparent molding compositions based on polyamide, impact modifier and short glass fibers and use thereof
Patent Information
- Application Number
- CN202180077706.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-19
- Filing Date
- 2021-11-16
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-11-16
Smart Images

Figure BDA0004235049120000231 
Figure BDA0004235049120000241 
Figure BDA0004235049120000251
Abstract
Description
[0001] This invention relates to a transparent molding composition based on a mixture of semi-crystalline aliphatic polyamide (with an average carbon number greater than or equal to 8 relative to nitrogen atoms) and amorphous polyamide, impact modifier, short glass fiber, and optionally prepolymer, wherein the mixture of polyamide, impact modifier, short glass fiber, and prepolymer has a refractive index between 1.500 and 1.540, the composition is free of PEBA and has a high modulus, particularly greater than 1700 MPa; and relates to the use of the composition in the production of injection-grown articles, particularly for articles used in sporting goods or electronic products.
[0002] The sports and electronics markets currently demand molding compositions based on transparent polyamides that exhibit high modulus, particularly at least 1700 MPa, after molding, as well as good impact strength, at least 70% transmittance on a 2 mm wafer, and good fatigue resistance, particularly for the sports market, and good grease resistance for the electronics market.
[0003] Patent EP3,309,199B1 describes a composition comprising a mixture of amorphous copolyamide and optional semi-crystalline polyamide and glass filler. This composition exhibits high transparency but low impact strength.
[0004] Patent FR3,018,280B1 describes compositions comprising semi-crystalline polyamide, amorphous polyamide, glass fiber, and optionally PEBA. These compositions exhibit low transmittance and slight haze. However, no information is given regarding modulus, impact properties, or fatigue resistance.
[0005] Application EP3,486,287A1 describes a composition comprising a semi-crystalline polyamide, an impact modifier, and glass fiber S.
[0006] These compositions exhibit good fatigue strength, but have high haze and no information is given regarding transmittance.
[0007] None of the above compositions satisfy the following three and / or four properties:
[0008] - Transmittance greater than 70% or haze less than 50%
[0009] - Modulus greater than 1700 MPa
[0010] - Good impact strength and / or fatigue strength.
[0011] Therefore, the present invention relates to a transparent molding composition comprising, by weight (total 100%):
[0012] (A) 35% to 84% of a polyamide mixture, comprising:
[0013] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0014] -90% to 5% by weight of at least one amorphous polyamide;
[0015] (B) 10 to 30%, particularly 15 to 30%, of at least one impact modifier;
[0016] (C) 6 to 20% short glass fibers; and
[0017] (D) 0 to 10% of at least one prepolymer;
[0018] (E) 0 to 5%, particularly 0.1 to 5%, of at least one additive selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0019] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0020] The composition is free of polyether block amide (PEBA) and has a dry modulus of over 1700 MPa at 23°C.
[0021] Therefore, the inventors unexpectedly discovered that by adding short glass fibers within a specific range to a mixture of amorphous and semi-crystalline polyamides within a specific range, and adding them together with at least one optional prepolymer to a specific range of impact modifiers, the refractive index of each component of the short glass fibers, the mixture of amorphous and semi-crystalline polyamides, the impact modifier, and the prepolymer can be such that a composition having a high modulus greater than 1700 MPa, high transmittance and / or slight haze, as well as good impact strength and / or good fatigue strength can be obtained.
[0022] In the context of this invention, amorphous polyamide refers to a transparent amorphous polyamide that possesses only a glass transition temperature (rather than a melting temperature (Tm)), or a polyamide with very low crystallinity, having a glass transition temperature and melting point such that, as measured according to standard ISO 11357-3:2013, the enthalpy of crystallization during a cooling step in differential scanning calorimetry (DSC) at a rate of 20 K / min is less than 30 J / g, particularly less than 20 J / g, and preferably less than 15 J / g. According to standards ISO 11357-1:2009 and ISO 11357-2:2013, the glass transition temperature (Tg) of these polyamides, measured by DSC at a heating rate of 20 K / min, is greater than 75 °C.
[0023] In the context of this invention, semi-crystalline polyamide means a polyamide having a melt temperature (Tm) by DSC according to ISO standard 11357-3:2013, and a crystallization enthalpy of greater than 30 J / g, preferably greater than 40 J / g, by DSC at a rate of 20 k / min according to ISO standard 11357-3 (2013).
[0024] The nomenclature used to define polyamides is described in ISO standard 1874-1:2011 “Plastics—Polyamide (PA) Moulding and Extrusion Materials—Part 1: Designation” and is well known to those skilled in the art.
[0025] The term "polyamide" as used in this specification includes both homopolymer and copolymer.
[0026] In one embodiment, the composition according to the invention is a thermoformable composition.
[0027] Regarding the excluded PEBA:
[0028] Polyether block amide (PEBA) is a copolymer having amide units (Ba1) and polyether units (Ba2), wherein the amide units (Ba1) correspond to units selected from at least one amino acid or from at least one lactam, or aliphatic repeating units of units XY obtained by the following condensation polymerization:
[0029] - At least one diamine, said diamine being selected from straight-chain or branched aliphatic diamines, or aromatic diamines or mixtures thereof, and
[0030] - At least one dicarboxylic acid, wherein the dicarboxylic acid is selected from aliphatic diacids or aromatic diacids.
[0031] The polyether unit (Ba2) is specifically derived from at least one polyalkylene ether polyol, especially polyalkylene polyether diol.
[0032] For component A:
[0033] semi-crystalline polyamide
[0034] Component (A) contains 10 to 95% semi-crystalline aliphatic polyamide.
[0035] Advantageously, component (A) contains 15 to 90% by weight of a semi-crystalline aliphatic polyamide.
[0036] More advantageously, component (A) contains 20 to 85% by weight of a semi-crystalline aliphatic polyamide.
[0037] Even more advantageously, component (A) contains 25 to 80% by weight of semi-crystalline aliphatic polyamide.
[0038] Specifically, component (A) contains 30 to 75% by weight of semi-crystalline aliphatic polyamide.
[0039] The at least one semi-crystalline aliphatic polyamide is obtained by the polycondensation of at least one lactam, or by the polycondensation of at least one amino acid, or by the polycondensation of at least one diamine Xa and at least one dicarboxylic acid Ya.
[0040] The average number of carbon atoms in the nitrogen atom of a semi-crystalline aliphatic polyamide is greater than or equal to 8.
[0041] In particular, the average number of carbon atoms in nitrogen atoms in semi-crystalline aliphatic polyamides is between 8 and 14.
[0042] Advantageously, the average number of carbon atoms in the nitrogen atom of the semi-crystalline aliphatic polyamide is greater than or equal to 9.
[0043] In particular, the average number of carbon atoms in the nitrogen atom of semi-crystalline aliphatic polyamides is between 9 and 14.
[0044] More advantageously, the average number of carbon atoms in the nitrogen atom of the semi-crystalline aliphatic polyamide is greater than or equal to 10.
[0045] In particular, the average number of carbon atoms in the nitrogen atom of semi-crystalline aliphatic polyamides is between 10 and 14.
[0046] In the case of PA-Xa·Ya homopolymer, the number of carbon atoms per nitrogen atom is the average of that of unit Xa and unit Ya.
[0047] In the case of copolyamides, the number of carbon atoms per nitrogen atom is calculated using the same principle. The molar ratio of the various amide units is used in this calculation.
[0048] In one embodiment, the semi-crystalline aliphatic polyamide is a mixture of two semi-crystalline aliphatic polyamides having an average number of carbon atoms relative to nitrogen atoms between 8 and 14, particularly between 9 and 14, and particularly between 10 and 14.
[0049] When the at least one semi-crystalline aliphatic polyamide is obtained by the polycondensation of at least one lactam, it may therefore include a single lactam or several lactams.
[0050] Advantageously, the at least one semi-crystalline aliphatic polyamide is obtained by polycondensation of a single lactam, and the lactam is selected from autolactam, laurolactam and undecyllactam, and is advantageously selected from laurolactam.
[0051] Clearly, if a lactam has an average number of carbon atoms less than or equal to 8 relative to the nitrogen atoms of a semi-crystalline aliphatic polyamide, it will subsequently be in the form of a copolyamide with another amino acid, lactam, or PAXaYa, such that the copolyamide has an average number of carbon atoms greater than or equal to 8 relative to the nitrogen atoms.
[0052] When the at least one semi-crystalline aliphatic polyamide is obtained by polycondensation of at least one amino acid, the at least one amino acid may be selected from C6 to C18, preferably C10 to C18, and more preferably C10 to C12 amino acids.
[0053] C6-C12 amino acids, especially 6-aminohexanoic acid, 9-aminononanoic acid, 10-aminodecanoic acid, 10-aminoundecanoic acid, 12-aminododecanoic acid and 11-aminoundecanoic acid and their derivatives, especially N-heptyl-11-aminoundecanoic acid.
[0054] Clearly, if an amino acid has an average number of carbon atoms less than or equal to 8 relative to the nitrogen atom in a semi-crystalline aliphatic polyamide, it will subsequently be in the form of a copolyamide with another amino acid, lactam, or PAXaYa, such that the copolyamide has an average number of carbon atoms greater than or equal to 8 relative to the nitrogen atom.
[0055] When the at least one semi-crystalline aliphatic polyamide is obtained by the polycondensation of at least one amino acid, it may include a single amino acid or several amino acids.
[0056] Advantageously, the semi-crystalline aliphatic polyamide is obtained by the polycondensation of a single amino acid, and the amino acid is selected from 11-aminoundecanoic acid and 12-aminododecanoic acid, advantageously selected from 11-aminoundecanoic acid.
[0057] When the at least one semi-crystalline aliphatic polyamide is obtained by polycondensation of at least one diamine Xa and at least one diacid Ya, then the diamine is C4-C36, preferably C5-C18, preferably C5-C12, more preferably C10-C12, and the diamine is at least one C4-C36, preferably C6-C18, preferably C6-C12, more preferably C10-C12 diacid Ya, and the at least one diamine Xa is an aliphatic diamine, and the at least one diacid Ya is an aliphatic diacid.
[0058] Diamines can be linear or branched. Advantageously, they are linear.
[0059] The at least one C4-C36 diamine Xa may be particularly selected from 1,4-butanediamine, 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, 1,12-dodecanediamine, 1,13-tetridemethylenediamine, 1,14-tetradecanemethylenediamine, 1,16-hexadecanemethylenediamine, and 1,18-octadecanemethylenediamine, octadecenediamine, eicosanediamine, docosanediamine, and diamines obtained from fatty acids.
[0060] Advantageously, the at least one diamine Xa is C5-C18 and is selected from 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, 1,12-dodecamethylenediamine, 1,13-tetridemethylenediamine, 1,14-tetradecamethylenediamine, 1,16-hexadecamethylenediamine, and 1,18-octadecamethylenediamine.
[0061] Advantageously, the at least one C5-C12 diamine Xa is particularly selected from 1,5-pentamethylenediamine, 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, and 1,12-dodecamethylenediamine.
[0062] Advantageously, the at least one C6-C12 diamine Xa is particularly selected from 1,6-hexamethylenediamine, 1,7-heptamethylenediamine, 1,8-octamethylenediamine, 1,9-nonamethylenediamine, 1,10-decamethylenediamine, 1,11-undecamethylenediamine, and 1,12-dodecimethylenediamine.
[0063] Advantageously, the diamine Xa used is a C10-C12 diamine, particularly selected from 1,10-decamethylenediamine, 1,11-undecamethylenediamine, and 1,12-dodecimethylenediamine.
[0064] The at least one dicarboxylic acid Ya is C4-C36 and may be selected from succinic acid, glutaric acid, adipic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, dodecanoic acid, brassic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, octadecanoic acid and diacids obtained from fatty acids.
[0065] Dicarboxylic acids can be linear or branched. Advantageously, they are linear.
[0066] Advantageously, the at least one dicarboxylic acid Ya is C6-C18, and is selected from succinic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, dodecanoic acid, brassic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, and octadecanoic acid.
[0067] Advantageously, the at least one dicarboxylic acid Ya is C6-C12, and is selected from succinic acid, octanoic acid, azelaic acid, sebacic acid, undecanoic acid, and dodecanoic acid.
[0068] Advantageously, the at least one dicarboxylic acid Ya is C10-C12 and is selected from sebacic acid, undecanoic acid and dodecanoic acid.
[0069] Clearly, if diamine Xa has an average number of carbon atoms less than or equal to 8 relative to the nitrogen atoms of a semi-crystalline aliphatic polyamide, it will subsequently associate with dicarboxylic acid, such that the copolyamide has an average number of carbon atoms greater than or equal to 8 relative to the nitrogen atoms, and vice versa.
[0070] Polyamide XaYa may also have an average number of carbon atoms less than or equal to 8 relative to the nitrogen atoms of a semi-crystalline aliphatic polyamide, but it will subsequently be in the form of a copolyamide, such that the copolyamide has an average number of carbon atoms greater than or equal to 8 relative to the nitrogen atoms.
[0071] When the semi-crystalline aliphatic polyamide is obtained by polycondensation of at least one diamine Xa and at least one dicarboxylic acid Ya, it may include a single diamine or several diamines and a single dicarboxylic acid or several dicarboxylic acids.
[0072] In one embodiment, the semi-crystalline aliphatic polyamide is obtained by polycondensation of a single diamine Xa and a single dicarboxylic acid Ya.
[0073] Advantageously, the semi-crystalline aliphatic polyamide is selected from PA10, PA11, PA12, PA1010, PA1012, especially PA11 and PA12.
[0074] Advantageously, semi-crystalline polyamides are of partial or complete biological origin.
[0075] amorphous polyamide
[0076] Component (A) also contains 5 to 90% of at least one amorphous polyamide.
[0077] Advantageously, component (A) contains 10 to 85% amorphous polyamide.
[0078] More advantageously, component (A) contains 15 to 80% amorphous polyamide.
[0079] Even more advantageously, component (A) contains 20 to 75% amorphous polyamide.
[0080] Specifically, component (A) comprises 25 to 70% amorphous polyamide.
[0081] The amorphous polyamide is a polyamide having the formula XY or A / XY, wherein:
[0082] -A is a repeating aliphatic unit selected from units obtained by the condensation polymerization of at least one amino acid, units obtained by the condensation polymerization of at least one lactam, and units obtained by the condensation polymerization of at least one aliphatic diamine with at least one aliphatic diacid.
[0083] -X is at least one alicyclic diamine, and
[0084] -Y is at least one dicarboxylic acid, wherein the dicarboxylic acid is selected from straight-chain or branched aliphatic diacids, alicyclic diacids, and aromatic diacids.
[0085] The diamine and the diacid contain 4 to 36 carbon atoms, advantageously 6 to 18 carbon atoms.
[0086] Advantageously, the amorphous polyamide is a polyamide of formula A / XY. The amino acid, lactam, diamine, and dicarboxylic acid constituting unit A are as defined for semi-crystalline aliphatic polyamides as defined above.
[0087] Amorphous polyamides can be homopolymers or copolymers.
[0088] The preferred molar ratio of diamine X and dicarboxylic acid Y is stoichiometric.
[0089] Dicarboxylic acids contain 4 to 36 carbon atoms, and advantageously contain 6 to 18 carbon atoms.
[0090] Alicyclic diamines may be selected from, for example, bis(3,5-dialkyl-4-aminocyclohexyl)methane, bis(3,5-dialkyl-4-aminocyclohexyl)ethane, bis(3,5-dialkyl-4-aminocyclohexyl)propane, bis(3,5-dialkyl-4-aminocyclohexyl)butane, bis(3-methyl-4-aminocyclohexyl)methane or 3′-dimethyl-4,4′-diamino-dicyclohexylmethane commonly referred to as “BMACM” or “MACM” (and hereinafter referred to as B), p-bis(aminocyclohexyl)methane commonly referred to as “PACM” (and hereinafter referred to as P), isopropylidene di(cyclohexylamine) commonly referred to as “PACP”, isophorone diamine (hereinafter referred to as IPD) and 2,6-bis(aminomethyl)norbornene commonly referred to as “BAMN”.
[0091] A non-exhaustive list of these alicyclic diamines can be found in the publication “Cycloaliphatic Amines” (Encyclopaedia of Chemical Technology, Kirk-Othmer, 4th Edition (1992), pp. 386–405).
[0092] Dicarboxylic acids can be selected from straight-chain or branched aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, and aromatic dicarboxylic acids.
[0093] When the dicarboxylic acid Y is aliphatic and linear, it is as defined above for diacid Ya.
[0094] When the dicarboxylic acid Y is alicyclic, it may contain the following carbon skeletons: norbornylmethane, cyclohexane, cyclohexylmethane, dicyclohexylmethane, dicyclohexylpropane, di(methylcyclohexyl) or di(methylcyclohexyl)propane.
[0095] When the dicarboxylic acid Y is aromatic, it can be selected from terephthalic acid (denoted as T), isophthalic acid (denoted as I), and naphthalic acid.
[0096] Advantageously, the dicarboxylic acid Y is aromatic; it can be selected from terephthalic acid (denoted as T) and isophthalic acid (denoted as I).
[0097] Advantageously, amorphous polyamides are of partial or complete biological origin.
[0098] Advantageously, the semi-crystalline aliphatic polyamides and / or semi-crystalline polyamides are of partial or complete biological origin.
[0099] Advantageously, the amorphous polyamide is selected from 11 / B10, 12 / B10, 11 / P10, 12 / P10, 11 / BI / BT, 12 / BI / BT, 11 / PI / BT, 12 / PI / BT, 11 / PI / PT, 12 / PI / PT, 11 / BI, 12 / BI, 11 / PI and 12 / PI, especially 11 / B10.
[0100] Advantageously, the semi-crystalline aliphatic polyamide is selected from PA10, PA11, PA12, PA1010, PA1012, especially PA11 and PA12, and the amorphous polyamide is selected from 11 / B10, 12 / B10, 11 / P10, 12 / P10, 11 / BI / BT, 12 / BI / BT, 11 / PI / BT, 12 / PI / BT, 11 / PI / PT, 12 / PI / PT, 11 / BI, 12 / BI, 11 / PI and 12 / PI, especially 11 / B10.
[0101] Advantageously, the semi-crystalline aliphatic polyamide is PA11, and the amorphous polyamide is selected from 11 / B10, 12 / B10, 11 / P10, 12 / P10, 11 / BI / BT, 12 / BI / BT, 11 / PI / BT, 12 / PI / BT, 11 / PI / PT and 12 / PI / PT, especially 11 / B10 and 12 / BI / BT.
[0102] Regarding impact modifier (B):
[0103] PEBA is excluded from the definition of impact modifier.
[0104] The impact modifier is present at 10% to 30% by weight, particularly 15% to 30% by weight, relative to the total weight of the composition.
[0105] Impact modifiers can be any type of impact modifier, as long as it is a polymer with a modulus lower than that of the resin and good adhesion to the matrix in order to dissipate cracking energy.
[0106] Impact modifiers are advantageously composed of polymers, particularly polyolefins, having a flexural modulus of less than 100 MPa as measured according to standard ISO 178 and a Tg of less than 0 °C (measured at the inflection point of the DSC thermogram according to standard 11357-2).
[0107] The impact modifier polyolefin can be functionalized or non-functionalized, or a mixture of at least one functionalized polyolefin and / or at least one non-functionalized polyolefin. For simplicity, the polyolefin is denoted as (B), and functionalized polyolefin (B1) and non-functionalized olefin (B2) are described below.
[0108] It is evident that some (e.g., but not limited to) homopolymers of polyethylene or polypropylene among the polyolefins described below have a refractive index less than 1.500. In this case, the polyolefin cannot be used alone and must be blended with one or more other polyolefins such that the mixture has a refractive index between 1.500 and 1.540.
[0109] Nonfunctionalized polyolefins (B2) are typically homopolymers or copolymers of α-olefins or dienes, such as ethylene, propylene, 1-butene, 1-octene, and butadiene. For example, one could mention:
[0110] - Homopolymers and copolymers of polyethylene, especially LDPE, HDPE, LLDPE (linear low-density polyethylene), VLDPE (very low-density polyethylene) and metallocene polyethylene.
[0111] - Homopolymers or copolymers of propylene.
[0112] 1) Ethylene / α-olefin copolymers such as ethylene / propylene, EPR (an abbreviation for ethylene-propylene-rubber) and ethylene / propylene / diene (EPDM).
[0113] - Styrene / ethylene-butene / styrene (SEBS), styrene / butadiene / styrene (SBS), styrene / isoprene / styrene (SIS), styrene / ethylene-propylene / styrene (SEPS) block copolymers.
[0114] - A copolymer of ethylene with at least one product selected from salts or esters of unsaturated carboxylic acids such as alkyl methacrylates (e.g., methyl acrylate), or vinyl esters of saturated carboxylic acids such as vinyl acetate (EVA), wherein the proportion of comonomers can reach 40% by weight.
[0115] Functionalized polyolefins (B1) can be polymers of α-olefins having reactive units (functional groups); such reactive units are acid, acid anhydride, or epoxy functional groups. For example, reference can be made to the aforementioned polyolefins (B2) grafted or copolymerized or trimerized by unsaturated epoxides such as (meth)acrylate, or by carboxylic acids or corresponding salts or esters such as (meth)acrylic acid (which can be completely or partially neutralized by metals such as Zn), or even by carboxylic anhydrides such as maleic anhydride.
[0116] The functionalized polyolefin (B1) may be selected from the following (co)polymers grafted with maleic anhydride or glycidyl methacrylate (wherein the grafting rate is, for example, 0.01 to 5% by weight):
[0117] -PE, PP, copolymers of ethylene with propylene, butene, hexene or octene, containing, for example, 35 to 80% by weight of ethylene;
[0118] 1) Ethylene / α-olefin copolymers such as ethylene / propylene, EPR (an abbreviation for ethylene-propylene-rubber) and ethylene / propylene / diene (EPDM).
[0119] - Styrene / ethylene-butene / styrene (SEBS), styrene / butadiene / styrene (SBS), styrene / isoprene / styrene (SIS), styrene / ethylene-propylene / styrene (SEPS) block copolymers.
[0120] - Ethylene and vinyl acetate copolymer (EVA) containing up to 40% by weight of vinyl acetate;
[0121] - An ethylene and (meth)acrylate alkyl copolymer containing up to 40% by weight of (meth)acrylate alkyl ester;
[0122] - Ethylene and vinyl acetate (EVA) and alkyl methacrylate copolymers, containing up to 40% by weight of comonomers.
[0123] Functionalized polyolefins (B1) may also be selected from ethylene / propylene copolymers having a dominant maleic anhydride-grafted ethylene / propylene (the product described in EP-A-0,342,066) subsequently condensed with a monoamine polyamide (or a polyamide oligomer).
[0124] Functionalized polyolefins (B1) may also be copolymers or terpolymers of at least the following units: (1) ethylene, (2) vinyl esters or alkyl esters of saturated carboxylic acids and (3) anhydrides such as maleic anhydride or (meth)acrylic acid or (meth)acrylic acid epoxy such as glycidyl ester.
[0125] As an example of the latter type of functionalized polyolefin, the following copolymers (in which ethylene preferably accounts for at least 60% by weight of the copolymer, and in which the ternary monomer (functional group) accounts for, for example, 0.1 to 10% by weight of the copolymer) can be mentioned:
[0126] - Ethylene / (meth)acrylate alkyl ester / (meth)acrylic acid or maleic anhydride or glycidyl methacrylate copolymer;
[0127] - Ethylene / vinyl acetate / maleic anhydride or glycidyl methacrylate copolymer;
[0128] - Ethylene / vinyl acetate or (meth)acrylate alkyl ester / (meth)acrylic acid or maleic anhydride or glycidyl methacrylate copolymer.
[0129] In the aforementioned copolymers, (meth)acrylic acid can be saponified with Zn or Li.
[0130] The term “(meth)acrylate alkyl ester” in (B1) or (B2) means C1-C8 alkyl methacrylate and C1-C8 alkyl acrylate, and may be selected from methyl acrylate, ethyl acrylate, n-butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, methyl methacrylate and ethyl methacrylate.
[0131] In addition, the aforementioned polyolefin (B1) can also be crosslinked by any suitable method or reagent (diepoxide, diacid, peroxide, etc.); the term functionalized polyolefin also includes a mixture of the aforementioned polyolefin with a bifunctional reagent (such as diacid, dianhydride, diepoxide, etc.) that can react with these, or a mixture of at least two functionalized polyolefins that can react together.
[0132] The copolymers (B1) and (B2) described above can be copolymerized in a statistical or sequential manner and have linear or branched structures.
[0133] The molecular weight, melt flow index (MFI), and density of these polyolefins can vary widely, as those skilled in the art will know. MFI (Melt Flow Index) is a measure of fluidity in the molten state. It is measured according to standard ASTM 1238.
[0134] Advantageously, the functionalized polyolefin (B1) is selected from styrene / ethylene-butene / styrene (SEBS), styrene / butadiene / styrene (SBS), styrene / isoprene / styrene (SIS), and styrene / ethylene-propylene / styrene (SEPS) block copolymers grafted with maleic anhydride or glycidyl methacrylate, wherein the grafting degree is, for example, 0.01 to 5 by weight.
[0135] For example, it can be FG 1901 (SEBS-functionalized maleic anhydride) 9901 (SEBS-functionalized maleic anhydride) (SEBS maleic anhydride).
[0136] The MFI of polyamides, and the MFI of (B1) and (B2) can be selected within a wide range; however, it is recommended that the MFI of polyamide be greater than that of (B) to promote the dispersion of (B).
[0137] Impact modifiers can also be core-shell structures.
[0138] The core and shell are preferably in the form of spherical polymer particles. These particles are also called core-shell particles or core-shell polymers. The first layer forms the core, and the second or all subsequent layers form the corresponding shell.
[0139] The core and shell can be functionalized or unfunctionalized. When the core and shell are functionalized, this allows for better compatibility with the polyamide matrix of the invention. As an example, maleic anhydride-type functionalization is preferred.
[0140] As for the spherical polymer particle size, it has an average particle size by weight between 20 nm and 500 nm. Preferably, the weight-average particle size of the polymer is between 20 nm and 400 nm, more preferably between 20 nm and 350 nm, and advantageously between 20 nm and 300 nm.
[0141] The polymer particles have a multilayer structure, including at least one layer (F) and another layer (G), wherein the at least one layer (F) comprises a polymer (F1) with a glass transition temperature below 0°C, and the other layer (G) comprises a polymer (G1) with a glass transition temperature above 60°C.
[0142] Preferably, the polymer (G1) with a glass transition temperature greater than 60°C is the outer layer of polymer particles with a multilayer structure.
[0143] Polymer particles are obtained through multi-step methods, such as using two, three, or more steps.
[0144] Preferably, the polymer (F1) in layer (F) with a glass transition temperature below 0°C is produced in the first step of a multi-step process for forming the core of polymer particles with a multilayer structure. Preferably, the polymer (F1) has a glass transition temperature below -5°C, more preferably below -15°C, and advantageously below -25°C.
[0145] Preferably, the polymer (G1) with a glass transition temperature greater than 60°C is produced in the final step of a multi-step process for forming the outer layer of polymer particles with a multi-layered structure.
[0146] There may be one or more additional intermediate layers obtained through one or more intermediate steps.
[0147] The glass transition temperature (Tg) of multilayer polymers can be estimated, for example, by dynamic methods such as thermomechanical analysis.
[0148] The polymer (F1) and layer (F) contain 0% to less than 50% by weight of monomers containing aromatic groups. The polymer (G1) and layer (G) contain 0% to less than 50% by weight of monomers containing aromatic groups.
[0149] According to one embodiment, the polymer (G1) and the layer (G) do not include monomers containing aromatic groups.
[0150] Regarding the polymer (F1) with a glass transition temperature below 0°C, it comprises at least 50% by weight polymer units derived from isoprene or butadiene, and the layer (F) is the innermost layer of the polymer particle having a multilayer structure. In other words, the layer (F) containing the polymer (F1) is the core of the polymer particle.
[0151] For example, the polymer (F1) of the core may consist of isoprene homopolymer or butadiene homopolymer, isoprene-butadiene copolymer, isoprene copolymer having up to 98% by weight of vinyl monomers, and butadiene copolymer having up to 98% by weight of vinyl monomers. The vinyl monomers may be styrene, alkylstyrene, acrylonitrile, alkyl (meth)acrylate, or butadiene or isoprene, or mixtures thereof, provided that the polymer (F1) contains less than 50% by weight of monomers containing aromatic groups.
[0152] The polymer (F1) may be crosslinked. Crosslinking monomers that can be used in this invention include, but are not limited to, aromatic polyfunctional vinyl compounds such as divinylbenzene and divinyltoluene; polyols such as ethylene glycol dimethacrylate and 1,3-butanediol diacrylate; trimethacrylates; triacrylates; allyl carboxylate esters such as allyl acrylate and allyl methacrylate; and diallyl and triallyl compounds such as diallyl phthalate, diallyl sebacate, and triallyl triazine.
[0153] According to one embodiment, the core is a butadiene homopolymer.
[0154] According to another embodiment, the core is a butadiene-styrene copolymer.
[0155] More preferably, the polymer (F1) containing at least 50% by weight of polymeric units derived from isoprene or butadiene has a glass transition temperature (Tg) between -100°C and 10°C, even more preferably between -80°C and 0°C, and advantageously between -70°C and -20°C.
[0156] Regarding polymer (G1), reference may be made to homopolymers and copolymers comprising monomers containing double bonds and / or vinyl monomers. Preferably, said polymer (G1) is a (meth)acrylic polymer.
[0157] Preferably, the polymer (G1) comprises at least 70% by weight of a monomer selected from C1-C12 alkyl esters of (meth)acrylate. Even more preferably, the polymer (G1) comprises at least 80% by weight of C1-C4 alkyl ester monomers of methacrylate and / or C1-C8 alkyl ester monomers of acrylate.
[0158] Most preferably, the acrylic or methacrylic monomers of the polymer (G1) are selected from methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate and mixtures thereof, provided that the polymer (G1) has a glass transition temperature of at least 60°C.
[0159] The polymer (G1) may contain a functional monomer selected from glycidyl (meth)acrylate, acrylic acid or methacrylic acid, amides derived from these acids, such as dimethacrylamide, 2-methoxyethyl acrylate or 2-methoxyethyl methacrylate, and 2-aminoethyl acrylate or 2-aminoethyl methacrylate and mixtures thereof.
[0160] Advantageously, the polymer (G1) contains at least 70% by weight of monomer units derived from methyl methacrylate.
[0161] Preferably, the glass transition temperature (Tg) of the polymer (G1) is between 60°C and 150°C. More preferably, the glass transition temperature of the polymer (G1) is between 80°C and 150°C, advantageously between 90°C and 150°C, and even more advantageously between 100°C and 150°C.
[0162] Preferably, polymer (G1) is grafted onto the polymer produced in the previous step.
[0163] According to some implementations, the polymer (G1) is cross-linked.
[0164] The core and shell can be obtained by a method involving several steps, including at least two steps. Such methods are described, for example, in documents US2009 / 0149600 or EP0,722,961.
[0165] Preferably, the polymer (F1) with a glass transition temperature below 0°C prepared during step (F) is the first step of the multi-stage method.
[0166] The polymer (F1) of the layer included in step (F) has a weight ratio of at least 60% by weight, preferably at least 70% by weight, and more preferably at least 75% by weight relative to the total weight of the multilayer polymer.
[0167] In step (G), the outer polymer (G1) has a weight ratio of at least 5% by weight, preferably at least 6% by weight, and more preferably at least 7% by weight relative to the entire multilayer polymer.
[0168] According to the present invention, the ratio rb between the outer layer (G) containing polymer (B1) and the entire multilayer polymer is at most 30% by weight.
[0169] Preferably, the ratio of polymer (G1) to the entire multilayer polymer is between 5% by weight and 30% by weight.
[0170] Advantageously, the impact modifier is selected from SEBS, SBS and core-shell structures.
[0171] Regarding short glass fibers (C):
[0172] Short glass fibers are present in the composition at 6 to 20% by weight, particularly 6 to 15% by weight.
[0173] Short glass fibers can have circular or non-circular cross-sections.
[0174] A fiber with a circular cross-section is defined as a fiber whose distance from the center of the fiber is equal at any point on its circumference, thus representing a perfect or near-perfect circle.
[0175] Any glass fiber that does not possess a perfect or near-perfect circle is therefore defined as a fiber with a non-circular cross-section.
[0176] Non-limiting examples of non-circular cross-section fibers are non-circular fibers that have shapes such as elliptical, oval or cocoon-shaped, star-shaped, sheet-shaped, flat fibers, cross-shaped, polygonal and cyclic.
[0177] Before using the composition, the short glass fibers preferably have a length of 2 to 13 mm, more preferably 3 to 8 mm.
[0178] Fiberglass can:
[0179] - It either has a circular cross-section with a diameter between 4 μm and 25 μm, preferably between 4 μm and 15 μm.
[0180] - It either has a non-circular cross-section with an L / D ratio between 2 and 8, particularly between 2 and 4 (where L represents the maximum size of the fiber's cross-section and D represents the minimum size of the fiber's cross-section). L and D can be measured using a scanning electron microscope (SEM).
[0181] Regarding prepolymer (D):
[0182] At least one prepolymer is optionally present in 0 to 10% by weight relative to the total weight of the composition.
[0183] The term "prepolymer" refers to an oligomer of a polyamide that necessarily has a lower number-average molecular weight than the polyamide used in the matrix, particularly a number-average molecular weight of 1,000–15,000 g / mol, especially 1,000–10,000 g / mol.
[0184] The prepolymer may be selected from aliphatic, linear or branched polyamide oligomers, alicyclic polyamide oligomers, semi-aromatic polyamide oligomers, aromatic polyamide oligomers, and aliphatic, linear or branched, alicyclic, semi-aromatic and aromatic polyamides having the same definition as above.
[0185] Therefore, prepolymers or oligomers originate from the following condensation:
[0186] - at least one lactam, or
[0187] - at least one amino acid, or
[0188] - at least one diamine and at least one dicarboxylic acid, or
[0189] Its mixture.
[0190] Therefore, prepolymers or oligomers cannot correspond to the condensation of diamines with lactams or amino acids.
[0191] The prepolymer can also be a copolyamide oligomer or a mixture of polyamide and copolyamide oligomer.
[0192] For example, the prepolymer is monofunctional NH2, monofunctional CO2H, or bifunctional CO2H or NH2.
[0193] Therefore, the prepolymer can be a monofunctional or bifunctional acid or amine. That is, when it is monofunctional (in which case the other end is nonfunctional, especially CH3), it has a single terminal amine or acid functional group, or when it is bifunctional, it has two terminal amine functional groups or two terminal acid functional groups.
[0194] Advantageously, the prepolymer is monofunctional, preferably NH2 or CO2H.
[0195] It may also be nonfunctional, with two ends, especially double CH3.
[0196] Monofunctional NH2 prepolymers can be prepared by reacting alkyl groups (straight-chain or branched-chain), preferably COOH, or aryl monocarboxylic acids with NH2 or COOH after condensation of lactams, amino acids or diamines with dicarboxylic acids.
[0197] The bisNH2 prepolymer can be prepared by reacting the diamine with a dicarboxylic acid after the condensation of a lactam or amino acid or diamine.
[0198] Monofunctional CO2H prepolymers can be prepared by reacting alkyl groups (straight-chain or branched-chain), preferably COOH, or aryl monocarboxylic acids with NH2 or COOH after condensation of lactams, amino acids or diamines with dicarboxylic acids.
[0199] The bisCO2H prepolymer can be prepared by reacting the dicarboxylic acid after condensation of a lactam, amino acid, or diamine with the dicarboxylic acid.
[0200] Nonfunctional bisCH3 prepolymers can be prepared by reacting the amine terminus of the prepolymer with an alkyl monocarboxylic acid and by reacting the acid terminus with an alkylamine.
[0201] Advantageously, in the compositions of the present invention, the prepolymer is selected from long-chain polyamides and is compatible with the polyamide matrix, particularly the polyamide matrix being selected from long-chain polyamides, especially aliphatic, semi-aromatic or alicyclic polyamides.
[0202] Advantageously, the prepolymer corresponds to a polyamide, particularly an aliphatic polyamide, especially selected from PA6, PA11, PA12, PA11 / 6 and PA6 / 12 or mixtures thereof.
[0203] Advantageously, a single prepolymer is used in this composition.
[0204] The prepolymer used in the compositions of the present invention may have the following average molecular weights: 1,000 to 15,000 g / mol, particularly 1,000 to 13,000 g / mol, particularly 1,000 to 10,000 g / mol, particularly 1,000 to 9,000 g / mol, particularly 1,000 to 8,000 g / mol, particularly 1,000 to 7,000 g / mol, particularly 1,000 to 6,000 g / mol, particularly 1,000 to 5,000 g / mol, particularly 2,000 to 5,000 g / mol, particularly 2,000 to 4,000 g / mol, particularly 2,000 to 3,000 g / mol.
[0205] Advantageously, the prepolymer accounts for 0.1 to 10% by weight, particularly 1 to 10% by weight, preferably 1 to 7% by weight, more preferably 3 to 7% by weight, and even more preferably 5 to 7% by weight, relative to the total weight of the composition.
[0206] Advantageously, the prepolymer is selected from bisCH3, bisNH2, monoNH2, monoacid, diacid and amino acid prepolymers.
[0207] In particular, the prepolymer is a single NH2 or a single acid or a diacid, especially a single NH2.
[0208] The refractive index of each component (A), (B), (C) and (D) at 560 nm is between 1.500 and 1.540.
[0209] The refractive index was measured at 560 nm on an Abbe refractometer (NAR_1T SOLID model) from Atago at 23°C.
[0210] The refractive index of the fiber can be obtained from datasheets and / or literature.
[0211] Regarding additives (E):
[0212] At least one additive is optionally present in 0 to 5% by weight, particularly 0.1 to 5% by weight, relative to the total weight of the composition.
[0213] The at least one additive is selected from stabilizers, colorants, plasticizers, processing aids, or mixtures thereof.
[0214] It should be noted that the composition with added additives must maintain its transparency.
[0215] As an example, the stabilizer can be a UV stabilizer, an organic stabilizer, or a combination of more general organic stabilizers, such as phenolic antioxidants (e.g., Ciba-BASF's Irganox 245, 1098, or 1010 types), phosphite / ester antioxidants (e.g., Ciba-BASF's...). 126 or 168), or even optionally other stabilizers, such as HALS, which stands for hindered amine light stabilizer (e.g., Ciba-BASF's Tinuvin 770), UV stabilizer (e.g., Ciba's Tinuvin 312), and phosphorus-based stabilizers. Amine antioxidants such as Crompton's Naugard 445, or even multifunctional stabilizers such as Clariant's Nylostab S-EED, can also be used.
[0216] The stabilizer can also be a mineral stabilizer, such as a copper-based stabilizer. Examples of such mineral stabilizers include halides and copper acetate. Alternatively, other metals, such as silver, can be considered, but these are known to be less effective. These copper-based compounds typically associate with alkali metal halides, particularly potassium.
[0217] For example, plasticizers are selected from benzenesulfonamide derivatives, such as n-butylbenzenesulfonamide (BBSA); ethyl toluenesulfonamide or N-cyclohexyl toluenesulfonamide; hydroxybenzoic acid esters, such as 2-ethylhexyl p-hydroxybenzoate and 2-decyl hexyl p-hydroxybenzoate; esters or ethers of tetrahydrofurfuryl alcohol, such as oligoethyleneoxytetrahydrofurfuryl alcohol; and esters of citric acid or hydroxymalonic acid, such as oligoethyleneoxymalonic acid ester.
[0218] Mixtures using plasticizers will not exceed the scope of this invention.
[0219] About the composition:
[0220] The compositions of the present invention have a dry modulus of more than 1700 MPa at 23°C.
[0221] Distinguishing between different moduli (e.g., tensile modulus, flexural modulus, etc.). If we consider the flexural modulus, it is always lower than the tensile modulus.
[0222] These moduli may be affected by temperature and the moisture level in the sample.
[0223] In one embodiment, the modulus defined above corresponds to the flexural modulus and the tensile modulus, the flexural modulus being measured according to standard ISO 178:2010, and the tensile modulus (or elastic modulus E) being measured according to standards ISO 527-1 and 2:2012.
[0224] In another embodiment, the modulus defined above corresponds to the flexural modulus, and is measured as described above.
[0225] In another embodiment, the modulus defined above corresponds to the tensile modulus, and is measured as described above.
[0226] In one embodiment, the composition of the present invention has a flexural and tensile modulus greater than 1700 MPa measured dry at 23°C.
[0227] Advantageously, the flexural or tensile modulus measured dry at 23°C is greater than 1800 MPa.
[0228] Advantageously, the tensile modulus measured dry at 23°C exceeds 1900 MPa, and particularly 2000 MPa.
[0229] In one embodiment, the transparent molding composition of the present invention exhibits a transmittance of over 70% as measured according to ASTM D1003 on a 2mm thick plate with a width and length of 100mm x 100mm manufactured by the polyamide molding composition in an unpolished mold.
[0230] Advantageously, the transmittance exceeds 75%, especially greater than or equal to 80%.
[0231] In another embodiment, the transparent molding composition has a haze of less than 50%, particularly less than 40%, as measured according to ASTM D1003 on a 2mm thick plate with a width and length of 100mm x 100mm manufactured in an unpolished mold from said polyamide molding composition.
[0232] Advantageously, the haze level is less than or equal to 35%.
[0233] Advantageously, the transparent molding composition of the present invention has a transmittance of greater than 70% and a haze of less than 50%, particularly less than 40%, as measured according to ASTM D1003 on a 2mm thick plate with a width and length of 100mm x 100mm manufactured in an unpolished mold from said polyamide molding composition.
[0234] Advantageously, the transmittance is greater than 75%, particularly greater than or equal to 80%, and the haze is less than or equal to 35%.
[0235] In yet another embodiment, the transparent molding composition of the present invention has an impact resilience greater than 15 KJ / m², particularly greater than 17 KJ / m², as measured, according to ISO 179-1:2010 / 1eA (Charpy impact), on a dry sample at 23°C ± 2°C and 50% ± 10% relative humidity on a V-notched bar with dimensions of 80 mm × 10 mm × 4 mm.
[0236] The composition of the present invention is a transparent molding composition, which comprises (total 100%) by weight:
[0237] (A) 35% to 84% of a polyamide mixture, comprising:
[0238] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0239] -90% to 5% by weight of at least one amorphous polyamide;
[0240] (B) 10 to 30%, particularly 15 to 30%, of at least one impact modifier;
[0241] (C) 6 to 20% short glass fibers; and
[0242] (D) 0 to 10% of at least one prepolymer;
[0243] (E) 0 to 5%, particularly 0.1 to 5%, of at least one additive selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0244] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0245] The composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
[0246] Advantageously, the transparent molding composition is obtained from the following by weight (total 100%):
[0247] (A) 35% to 84% of a polyamide mixture, comprising:
[0248] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0249] -90% to 5% by weight of at least one amorphous polyamide;
[0250] (B) More than 10% to 30%, particularly 15% to 30%, of at least one impact modifier;
[0251] (C) 6 to 20% short glass fibers; and
[0252] (D) 0 to 10% of at least one prepolymer;
[0253] (E) 0 to 5%, particularly 0.1 to 5%, of at least one additive selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0254] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0255] The composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
[0256] In another embodiment, the transparent molding composition comprises (total 100%) the following by weight:
[0257] (A) 35% to 83% of a polyamide mixture, comprising:
[0258] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0259] -90% to 5% by weight of at least one amorphous polyamide;
[0260] (B) More than 10% to 30%, particularly 15% to 30%, of at least one impact modifier;
[0261] (C) 6 to 20% short glass fibers; and
[0262] (D) 1 to 10% of at least one prepolymer;
[0263] (E) 0 to 5%, particularly 0.1 to 5%, of at least one additive selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0264] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0265] The composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
[0266] In another embodiment, the transparent molding composition is prepared from the following by weight (total 100%):
[0267] (A) 35% to 83% of a polyamide mixture, comprising:
[0268] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0269] -90% to 5% by weight of at least one amorphous polyamide;
[0270] (B) More than 10% to 30%, particularly 15% to 30%, of at least one impact modifier;
[0271] (C) 6 to 20% short glass fibers; and
[0272] (D) 1 to 10% of at least one prepolymer;
[0273] (E) 0 to 5%, particularly 0.1 to 5%, of at least one additive selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0274] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0275] The composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
[0276] In yet another embodiment, the transparent molding composition comprises (total 100%) by weight:
[0277] (A) A polyamide mixture of 35% to 83.9% comprising:
[0278] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0279] -90% to 5% by weight of at least one amorphous polyamide;
[0280] (B) More than 10% to 30%, particularly 15% to 30%, of at least one impact modifier;
[0281] (C) 6 to 20% short glass fibers; and
[0282] (D) 0 to 10% of at least one prepolymer;
[0283] (E) 0.1% to 5% of at least one additive, said at least one additive being selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0284] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0285] The composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
[0286] Advantageously, it is produced from a total of 100% of the following:
[0287] (A) A polyamide mixture of 35% to 83.9% comprising:
[0288] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0289] -90% to 5% by weight of at least one amorphous polyamide;
[0290] (B) More than 10% to 30%, particularly 15% to 30%, of at least one impact modifier;
[0291] (C) 6 to 20% short glass fibers; and
[0292] (D) 0 to 10% of at least one prepolymer;
[0293] (E) 0.1% to 5% of at least one additive, said at least one additive being selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0294] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0295] The composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
[0296] In yet another embodiment, the composition comprises, and in yet another embodiment, the transparent molding composition comprises, by weight (total 100%):
[0297] (A) 35% to 82.9% of a polyamide mixture comprising:
[0298] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0299] -90% to 5% by weight of at least one amorphous polyamide;
[0300] (B) More than 10% to 30%, particularly 15% to 30%, of at least one impact modifier;
[0301] (C) 6 to 20% short glass fibers; and
[0302] (D) 1 to 10% of at least one prepolymer;
[0303] (E) 0.1% to 5% of at least one additive, said at least one additive being selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0304] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0305] The composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
[0306] Advantageously, it is produced from a total of 100% of the following:
[0307] (A) 35% to 82.9% of a polyamide mixture comprising:
[0308] -10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8;
[0309] -90% to 5% by weight of at least one amorphous polyamide;
[0310] (B) More than 10% to 30%, particularly 15% to 30%, of at least one impact modifier;
[0311] (C) 6 to 20% short glass fibers; and
[0312] (D) 1 to 10% of at least one prepolymer;
[0313] (E) 0.1% to 5% of at least one additive, said at least one additive being selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
[0314] The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.540.
[0315] The composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
[0316] In the first variant, a semi-crystalline aliphatic polyamide dominates the mixture (A), and in particular, it is contained in the mixture at 51% to 80% by weight.
[0317] Therefore, the term "dominant" means that in mixture (A), semi-crystalline aliphatic polyamide is present in the mixture at more than 50% and amorphous polyamide is present at less than 50%.
[0318] Therefore, amorphous polyamides are present in the mixture, specifically at 20% to 49%.
[0319] All embodiments of the composition detailed above are effective for this first variant.
[0320] Advantageously, in this first variant, the composition exhibits greater than 50,000 cycles of fatigue testing on unnotched Ross Flex at 23°C, as determined according to standard ASTM D1052 using unnotched and undrilled samples with a folding angle of 60°.
[0321] According to another aspect, the present invention relates to the use of the compositions defined above for the first variant for the production of articles obtained by injection, said articles being selected from sports articles, particularly sports boots, particularly ski boots or ski boot parts or hard shoes with anti-slip spikes (such as anti-slip spikes for soccer, rugby or football), hockey shoes or hockey shoe parts, or running shoes, golf balls or golf ball parts, or lacrosse sticks, hockey articles such as helmets, and sports articles for protecting the head, shoulders, elbows, hands, knees, back or shin, such as helmets, gloves, shoulder pads, elbow pads, knee pads or shin pads.
[0322] Advantageously, the composition of the first variant is used to manufacture the outsole of athletic shoes, thereby allowing the pattern and color of the middle outsole of the athletic shoe to be seen through the outsole due to its transparency.
[0323] In the second variant, amorphous polyamide is dominant in mixture (A), and in particular, it is contained in the mixture at 55% to 85% by weight.
[0324] Therefore, the term "dominant" means that in mixture (A), amorphous polyamide is present in the mixture at more than 50% and semi-crystalline aliphatic polyamide is present at less than 50%.
[0325] Therefore, semi-crystalline aliphatic polyamides are present in the mixture, specifically at 15% to 45%.
[0326] All embodiments of the composition described above are also effective for this second variant.
[0327] According to another aspect, the present invention relates to the use of compositions defined for the second variant in the manufacture of articles for use in electronic products, for telecommunications applications, or for data exchange (such as for autonomous vehicles or for applications to connect with each other).
[0328] According to another aspect, the present invention relates to a method for preparing a composition as defined above, comprising the step of mixing components (A), (B), (C), (D) and (E) in an extruder at a temperature of 230 to 330°C to produce granules, which are then injected on an injection press at a temperature between 230 and 330°C to produce desired articles.
[0329] Therefore, this preparation method involves all compositions defined above, whether they are general compositions or compositions of the first and second variants.
[0330] Transparent molded articles comprising compositions as defined above, such as fibers, cloths, films, sheets, rods, tubes, and injection molded parts, may be produced as dry mixtures or after compounding in an extruder.
[0331] Therefore, the article relates to all compositions defined above, whether they are general compositions or compositions of the first and second variations.
[0332] According to another aspect, the present invention relates to a molded composite article comprising: a resin element (I) comprising a composition as defined above and a resin element (II) comprising a composition containing a semi-crystalline thermoplastic polymer, a geothermal polyurethane (TPU) or a foamed or non-foamed polyether block amide (PEBA), wherein the resin element (I) is directly bonded to or incorporated into the resin element (II).
[0333] A method for producing a molded composite article as defined above, the method comprising heating at least one resin (I) and resin (II) to attach one resin to another resin. Example
[0334] Preparation and mechanical properties of the compositions of the present invention:
[0335] The compositions in Tables I and II were prepared by mixing molten polyamide granules with impact modifiers and short glass fibers, along with optional prepolymers and additives. The mixtures were prepared by compounding on an 18 mm diameter twin-screw co-rotation extruder with a flat temperature profile (T°) at 250 °C. The screw speed was 300 rpm and the flow rate was 8 kg / h.
[0336] The introduction of short glass fibers is carried out using a side feeder.
[0337] Polyamides, prepolymers, impact modifiers, and additives are added during the mixing process in the main hopper.
[0338] Subsequently, on an injection molding machine (Engel), the composition was molded into dumbbell shapes (see Table 3) or rod shapes at a setpoint temperature of 240°C for the supply, and at a molding temperature of 260°C for the nozzle and 60°C for the molding, in order to study the properties of the composition according to the following criteria.
[0339] The tensile modulus was measured on a type 1A dumbbell at 23°C according to ISO standard 527-1:2012.
[0340] The instrument used was an INSTRON 5966 model. For modulus measurement, the crosshead speed was 1 mm / min. The test conditions on the dry sample were 23℃ ± 2℃.
[0341] The composition is a dry composition.
[0342] Impact strength was determined according to ISO 179-1:2010 / 1eA (Charpy impact) on a V-notched bar with dimensions of 80 mm × 10 mm × 4 mm at a temperature of 23 °C ± 2 °C and a relative humidity of 50% ± 10%, or at a temperature of –30 °C ± 2 °C and a relative humidity of 50% ± 10% on a dry sample.
[0343] According to standard ISO 527-1:2012, elongation at break and tensile strength were measured on dry samples at 23°C.
[0344] Unnotched Ross Flex fatigue tests were conducted at 23°C according to standard ASTM D1052 09 (2014) (the difference being a folding angle of 60°). Parts 2 mm thick, 150 mm long, and 20 mm wide were prepared from the composition of this invention (EIn) or the comparative composition (ECn) and subsequently conditioned at 70°C and 62% relative humidity for 7 days. The cycle count was 100 / min.
[0345] The 100x100x2 mm³ wafer was injection molded for transmittance and haze measurement. The following parameters were used:
[0346] - Non-polished mold
[0347] -ENGEL VICTORY 500, 160T Hydraulic Press
[0348] - Injection temperature (feed / nozzle): 260℃ / 280℃
[0349] - Mold temperature: 60℃
[0350] - Duration: 20s
[0351] - Material holding pressure: 525 bar
[0352] -Cooldown time: 20s
[0353] [Table 1]
[0354]
[0355]
[0356]
[0357] [Table 2]
[0358]
[0359]
[0360] PA11: (Arkema)
[0361] PA11 / B10 (10:90 by weight)
[0362] Kraton TM FG 1901: A maleic anhydride-functionalized linear triblock copolymer based on styrene and ethylene / butene, d = 0.91 g / cm³, supplied by Kraton Polymers.
[0363] Paraloid TM EXL 2690: Methyl methacrylate-butadiene-styrene (MBS) core-shell copolymer
[0364] Additives: Antioxidant mixture (0.1 wt%) + auxiliary antioxidant (0.2 wt%)
[0365] Injectability and surface appearance were also determined.
[0366] The results are shown in Table 6 of Table 1.
[0367] [Table 3]
[0368]
[0369]
[0370] The EC 2 and EC 3 data are not from the applicant, but rather those data indicated in EP 3,309,199 B1 and EP 3,486,287A1, respectively.
[0371] [Table 4]
[0372]
[0373]
[0374] Type 1A dumbbells were obtained by injection molding on an Engel-type injection molding machine: [Table 5]
[0375]
[0376] [Table 6]
[0377]
Claims
1. A transparent molding composition comprising, by weight, a total of 100% of: (A) 35% to 84% of a polyamide mixture, comprising: - 10 to 95% by weight of at least one semi-crystalline aliphatic polyamide having an average number of carbon atoms relative to nitrogen atoms greater than or equal to 8; - 90% to 5% by weight of at least one amorphous polyamide; (B) 10 to 30% of at least one impact modifier; (C) 6 to 20% short glass fibers; and (D) 0 to 10% of at least one prepolymer; (E) 0 to 5% of at least one additive, said at least one additive being selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof. The refractive indexes of each component (A), (B), (C), and (D) are between 1.500 and 1.
540. The transparent molding composition is PEBA-free and has a dry modulus of over 1700 MPa at 23°C.
2. The transparent molding composition according to claim 1, characterized in that, The transparent molding composition contains, by weight, a total of 100% of: (B) 15 to 30% of at least one impact modifier.
3. The transparent molding composition according to claim 1, characterized in that, The transparent molding composition comprises, by weight, a total of 100% of: (E) 0.1 to 5% of at least one additive selected from stabilizers, dyes, plasticizers, processing aids, or mixtures thereof.
4. The transparent molding composition according to claim 1, characterized in that, The transmittance is greater than 70%, as measured according to ASTM D1003 on a 2mm thick plate with a width and length of 100 mm x 100 mm manufactured in an unpolished mold from the transparent molding composition.
5. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The haze is less than 50%, as determined according to ASTM D1003 on a 2mm thick plate with a width and length of 100 mm x 100 mm manufactured in an unpolished mold from the transparent molding composition.
6. The transparent molding composition according to claim 5, characterized in that, The haze is less than 40%, as determined according to ASTM D1003 on a 2mm thick plate with a width and length of 100 mm x 100 mm manufactured in an unpolished mold from the transparent molding composition.
7. The transparent molding composition according to any one of claims 1 to 4, characterized in that, Impact resilience greater than 15 KJ / m 2 According to ISO 179-1: 2010 / 1eA, Charpy impact, measured on a dry sample at 23°C ± 2°C and 50% ± 10% relative humidity on a V-notched bar with dimensions of 80 mm × 10 mm × 4 mm.
8. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The impact modifier is selected from SEBS, SBS and core-shell structures.
9. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The amorphous polyamide is a polyamide of formula XY or A / XY, wherein: - A is a repeating aliphatic unit selected from units obtained by polycondensation of at least one amino acid, units obtained by polycondensation of at least one lactam, and units obtained by polycondensation of at least one aliphatic diamine and at least one aliphatic diacid. - X is an alicyclic diamine, and -Y is a dicarboxylic acid, wherein the dicarboxylic acid is selected from straight-chain or branched aliphatic diacids, alicyclic diacids, and aromatic diacids. The diamine and the diacid contain 4 to 36 carbon atoms.
10. The transparent molding composition according to claim 9, characterized in that, The diamine and the diacid contain 6 to 18 carbon atoms.
11. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The amorphous polyamide is selected from 11 / B10, 12 / B10, 11 / P10, 12 / P10, 11 / BI / BT, 12 / BI / BT, 11 / PI / BT, 12 / PI / BT, 11 / PI / PT, 12 / PI / PT, 11 / BI, 12 / BI, 11 / PI and 12 / PI, where B represents 3,3'-dimethyl-4,4'-diamino-dicyclohexylmethane and P represents p-bis(aminocyclohexyl)methane.
12. The transparent molding composition according to claim 11, characterized in that, The amorphous polyamide is 11 / B10.
13. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The semi-crystalline aliphatic polyamide is a mixture of two semi-crystalline aliphatic polyamides with an average carbon number between 8 and 14 relative to nitrogen atoms.
14. The transparent molding composition according to claim 13, characterized in that, The semi-crystalline aliphatic polyamide is a mixture of two semi-crystalline aliphatic polyamides with an average carbon number between 9 and 14 relative to nitrogen atoms.
15. The transparent molding composition according to claim 14, characterized in that, The semi-crystalline aliphatic polyamide is a mixture of two semi-crystalline aliphatic polyamides with an average carbon number between 10 and 14 relative to nitrogen atoms.
16. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The semi-crystalline aliphatic polyamide is selected from PA10, PA11, PA12, PA1010, and PA1012.
17. The transparent molding composition according to claim 16, characterized in that, The semi-crystalline aliphatic polyamide is selected from PA11 and PA12.
18. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The semi-crystalline aliphatic polyamide is PA11, and the amorphous polyamide is selected from 11 / B10, 12 / B10, 11 / P10, 12 / P10, 11 / BI / BT, 12 / BI / BT, 11 / PI / BT, 12 / PI / BT, 11 / PI / PT and 12 / PI / PT, wherein B represents 3,3'-dimethyl-4,4'-diamino-dicyclohexylmethane and P represents p-bis(aminocyclohexyl)methane.
19. The transparent molding composition according to claim 18, characterized in that, The amorphous polyamide is selected from 11 / B10 and 12 / BI / BT.
20. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The semi-crystalline aliphatic polyamide and / or the amorphous polyamide are of partial or complete biological origin.
21. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The semi-crystalline aliphatic polyamide is present in the polyamide mixture (A) at a concentration of more than 50% by weight.
22. The transparent molding composition according to claim 21, characterized in that, The semi-crystalline aliphatic polyamide is contained in the polyamide mixture (A) at a weight of 51% to 80% by weight.
23. The transparent molding composition according to claim 21, characterized in that, The transparent molding composition exhibits a fatigue tolerance greater than 50,000 in the unnotched Ross Flex test at 23°C, determined according to standard ASTM D1052 using unnotched and undrilled samples and a bending angle of 60°.
24. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The amorphous polyamide is present in the polyamide mixture (A) at a concentration of more than 50% by weight.
25. The transparent molding composition according to any one of claims 1 to 4, characterized in that, The amorphous polyamide is contained in the polyamide mixture at a weight of 55% to 85% by weight.
26. Use of the transparent molding composition as defined in any one of claims 21 to 23 for the production of articles obtained by injection, said articles being selected from sports articles.
27. The use according to claim 26, characterized in that, The sporting articles are selected from: ski boots or hard shoes with anti-slip spikes, or running shoes, golf balls, or hockey products, and sporting articles for protecting the head, shoulders, elbows, hands, knees, back, or shins.
28. The use according to claim 27, characterized in that, The hockey-themed product is a helmet.
29. The use according to claim 27, characterized in that, The sports products used to protect the head, shoulders, elbows, hands, knees, back, or shin are selected from: helmets, gloves, shoulder pads, elbow pads, knee pads, or shin pads.
30. The use according to claim 26, characterized in that, The sporting goods are selected from: ski boot parts, hockey shoe parts, or golf ball parts.
31. The use according to claim 26, characterized in that, The sporting goods are selected from: hockey shoes or lacrosse sticks.
32. The use of the transparent molding composition according to claim 22 for manufacturing the outsole of athletic shoes, thereby allowing the pattern and color of the middle outsole of the athletic shoe to be seen through the outsole due to its transparency.
33. Use of the transparent molding composition as defined in claim 24 or 25 for the manufacture of articles for use in electronic products, for telecommunications applications, or for data exchange.
34. The use as described in claim 33, characterized in that, The article of manufacture for use in electronic products, for telecommunications applications, or for data exchange is selected from articles of manufacture for use in autonomous vehicles or for interconnection applications.
35. A method for preparing a transparent molding composition as defined in any one of claims 1 to 25, comprising the step of mixing components (A), (B), (C), (D) and (E) in an extruder at a temperature of 230 to 330°C to produce granules, which are then injected on an injection press at a temperature between 230 and 330°C to produce the desired article.
36. A transparent molded article comprising a transparent molding composition as defined in any one of claims 1 to 25.
37. The transparent molded article according to claim 36, which is prepared in the form of a dry mixture or after compounding on an extruder.
38. The transparent molded article according to claim 36, characterized in that, The transparent molded product is selected from fibers, cloth, film, sheet, rod, tube, or injection molded parts.
39. Molded composite articles, including: A resin element (I) comprising a transparent molding composition as defined in any one of claims 1 to 25, and a resin element (II) comprising a composition containing a thermoplastic polymer, wherein the resin element (I) is directly bonded to or attached to the resin element (II).
40. The molded composite article according to claim 39, characterized in that, The thermoplastic polymer is selected from thermoplastic polyurethane (TPU), expanded polyether block amide (PEBA), or non-expanded polyether block amide (PEBA).
41. A method for producing a molded composite article as defined in claim 39 or 40, the method comprising heating at least one resin element (I) and a resin element (II) to attach one resin element to another resin element.
Citation Information
Patent Citations
Graft copolymer on the basis of alpha-mono-olefin, its process of fabrication, its application for the fabrication of thermoplastic blends, thermoplastic blends obtained
EP0342066A1
Preparation of butadiene-based impact modifiers
EP0722961A1
Glass filler reinforced polyamide molding materials based on amorphous copolyamides
EP3309199B1
Semi-transparent polymer composite comprising a linear aliphatic polyamide
EP3486287A1
TRANSPARENT composition BASED ON POLYAMIDE FILLED WITH GLASS
FR3018280B1